(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. We conducted this study to measure hemodialysis adequacy and determine to what extent some Kidney Disease Outcomes Quality Initiative (KDOQI) goals are achieved in our patients. Materials and Methods. In a cross-sectional study in Fars province, Iran, we assessed 632 patients on hemodialysis in 15 dialysis centers. The Kt/V was calculated, and data on serum levels of albumin, cholesterol, and triglyceride, hemoglobin level, blood pressure, body weight, and body mass index were collected. The values were compared with the KDOQI recommended target values. Results. The mean age of the patients was 54.36 ± 16.34 years. The mean Kt/V was 0.97 ± 0.42, which was significantly higher in those who received 3 dialysis sessions per week than those on 2 dialysis sessions per week (P = .03). Only 32.1% of all patients achieved the Kt/V goal. Seventy-four percent of the patients had a serum albumin equal or greater than 4 g/dL. Hemoglobin levels were between 4.6 g/dL and 16.8 g/dL, and half of the patients had attainment of the hemoglobin target. Cholesterol target was reached in 40% of patients. Only 43 patients (6.8%) attained all targets recommended by the KDOQI guidelines. Conclusions. The target values, except for serum albumin, were not reached in our patients. We conclude that it is necessary to provide essential equipment of dialysis centers such as dialysis machine and trained staffs, and also to raise awareness of KDOQI goals among patients and physicians.